Pemberdayaan Ekonomi Pesantren melalui Penguatan Unit Usaha BUMP di Pondok Pesantren Pangeran Diponegoro - Zainal Muttaqin; Cinthiya Zakiah Arifah (Journal of Innovation and Contribution to Community Service, 2025)
This community service project aimed to strengthen the institutional capacity of the Pesantren-Owned Enterprise (BUMP) at Pondok Pesantren Pangeran Diponegoro Yogyakarta as an effort to develop pesantren-based economic empowerment. Using participatory and collaborative approaches, the team conducted problem identification, managerial assistance, entrepreneurship training, development of standard operating procedures (SOP), and mapping of business legalization strategies. The results indicate that although BUMP's financial contribution remains limited, its social and functional impacts are significant—especially in supporting pesantren operations, improving access to essential services for the pesantren community, and serving as a platform for student entrepreneurship learning. Moreover, community involvement in managing business units has strengthened pesantren’s socio-economic relationships with its surrounding environment. Major challenges such as funding limitations, human resource management, and business legality remain critical areas for long-term improvement. This activity successfully increased institutional awareness, operational capacity, and opened future opportunities for BUMP to grow as a sustainable and inclusive pesantren economic model